Students' Communication Skills In Solving Mathematical Literacy Problems Based On Mathematical Abilities - Ilmus Samawati; Ika Kurniasari (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
Communication is one of the important things in the learning process because there will be social interactions that can make learning more lively. Through communication, students can understand and interpret understanding of mathematical problems, not only calculation problems but also mathematical problems in everyday life. This research aims to describe students' communication skills in solving mathematical literacy problems based on mathematical abilities. This research is qualitative descriptive research. The subjects in this research were 27 students of class VIII in one of SMP Swasta in Sidoarjo. Subjects were given a mathematics ability test to categorize the subject's mathematical abilities into high, medium, and low-levels. The research data were obtained from the results of mathematics literacy tests and interviews conducted by 3 selected subjects. The results showed that 1) students with high mathematical abilities have a medium category of communication skills because students can fulfill the indicators of expression, interpretation, use of notations/symbols, and evaluation with correct answers without complete reasons, 2) students with medium mathematical abilities have a medium category of communication skills because students can fulfill the expression and interpretation indicators with correct answers along with correct and clear reasons, fulfill the indicators of using notations/symbols with correct answers without complete reasons, but students do not fulfill the evaluation indicators, and 3) students with low mathematical abilities have a very low category of communication skills because students can fulfill the expression and interpretation indicators with wrong answers but there is a reason, fulfill the indicators of using notations/symbols with correct answers but no reason, but students do not fulfill the evaluation indicators. Keywords: communication skills, written, mathematical literacy problems, mathematical abilities.